Incidencia de la capacidad de pago en el acceso a microcréditos en los comerciantes del mercado Florida norte de la ciudad de Guayaquil - Gómez Arreaga, Víctor Manuel (2018)
This project is focused on the analysis of the incidence in the payment capacity in the access to microcredits of the merchants who work in the La Florida Norte market located in the city of Guayaquil, for which a field investigation was carried out. through surveys directed to a sample of one hundred and eighty-three merchants, and in which it was demonstrated that at present there are many restrictions on the part of the financial institutions at the moment of granting credits to these people, being one of the primary reasons the scarce resources they have, the lack of level of indebtedness that the banking entities request, as well as the guarantees demanded by the same institutions. Jointly it was established that a large part of the surveyed merchants, unable to access loans within legally constituted banking entities, seek third parties to grant them illegally at high interest rates………..